2017
DOI: 10.1016/j.apenergy.2016.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Energy autonomy in residential buildings: A techno-economic model-based analysis of the scale effects

Abstract: An increasingly decentralized energy supply structure alongside economic incentives for increasing the level of self-generation and -consumption are encouraging (higher levels of) energy autonomy. Previous work in this area has focused on the technical and economic aspects of energy autonomy at distinct scales, from individual buildings, through neighbourhoods to districts. This paper employs a mixed integer linear program (MILP) to assess the effects of aggregation across these scales on the economics of ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…Community electricity generation and storage systems could consist of one larger installation paid for and utilized by the whole energy community rather than several distributed installations as assumed in this work. Including economies of scale for investments in community‐size, as compared to household‐size, items of equipment is of particular relevance if thermal generation, as exemplified by local combined heat and power plants, is included in the analysis, potentially making electricity self‐sufficiency more beneficial for larger aggregations of residential households, as compared to individual households …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community electricity generation and storage systems could consist of one larger installation paid for and utilized by the whole energy community rather than several distributed installations as assumed in this work. Including economies of scale for investments in community‐size, as compared to household‐size, items of equipment is of particular relevance if thermal generation, as exemplified by local combined heat and power plants, is included in the analysis, potentially making electricity self‐sufficiency more beneficial for larger aggregations of residential households, as compared to individual households …”
Section: Discussionmentioning
confidence: 99%
“…To provide frameworks and trajectories with the goal of establishing a more active role for electricity users in the energy system, a better understanding is needed as to what functions self‐consumption and the aggregation of electricity consumers on different scales will have in a future electricity system. Research has been conducted on the topics of energy autarky and self‐consumption on different scales, from individual buildings to neighborhoods and districts, as well as on the clustering of prosumers to optimize power grid operation and reduce costs . Community energy storage has been investigated in terms of economic benefits and possibilities to integrate renewable energy sources and demand‐side management .…”
Section: Introductionmentioning
confidence: 99%
“…Other than to mention that the economic optimization does not necessarily determine the most environmentally optimum configuration, other related weaknesses are not included here. Instead the reader is referred to Merkel et al (2015) and McKenna et al (2016), in which they are discussed at length.…”
Section: B Discussion Of Methodology and Further Workmentioning
confidence: 99%
“…Most of these studies employ optimisation and/or simulation approaches that depict the building's physical and thermal characteristics in detail yet do not differentiate between (types of) households. For a detailed discussion the reader is referred to McKenna et al (2016).…”
mentioning
confidence: 99%
“…A systematic review on the cost of CHP system for Europe, Asia, and the USA has been reported by Staffell et al The study concludes that a long-term target of $300-5000 for 1-2 kW fuel cell micro-CHP system is more realistic and attainable by 2020 [ total turb turbine sys system energy autonomy in residential buildings. A mixed integer linear program is utilized to minimize the system cost over the lifetime of various energy production systems such as micro-CHP, photovoltaic (PV), thermal and electrical storage, and boilers, at five distinct scales and for nine demand cases [22].…”
Section: Introductionmentioning
confidence: 99%